Silverlight Recipes: A Problem-Solution Approach (Second Edition) - Ghosh, Jit (Apress, 2013)
Silverlight Tools for Visual Studio 2010, Visual Studio 2010, and Microsoft Expression Blend 4 give you the power to design innovative and powerful Silverlight 4 user interfaces. They give you access to cutting-edge graphics, animation, rich controls, and data binding in the powerful XML Application Markup Language (XAML) declarative language. For application logic, you can continue to use all the usual Visual Studio 2010 features such as debugging and access to your favorite development language, like C# or VB, and dynamic languages such as IronPython, IronRuby, and Managed JScript. What is truly amazing is that the breadth of the .NET Framework for Silverlight including functionality such as multithreading, generics, LINQ, and extension methods, is included in such a diminutively sized browser plug-in. While rich Internet application (RIA) development tools have been around for a while, Silverlight 4 makes RIA development real for traditional developers letting them use their favorite tools and programming languages to create fabulous user experiences.